The Use of Animation Video for Vocabulary Mastery - Sofia Datun Hikmah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study discussed an important aspect in learning English, namely the vocabulary. The teachers must have an easy, practical and interesting way to teach the vocabulary. Animated videos are considered as the right medium and very useful for teaching. This research focused on the effective use of animated cartoon videos and increasing the use of animated videos in improving the students’ learning mastery at grade IIV of Mayang 01 Junior High School. The purpose of the study was to determine the effectiveness and significance of the implementation or not using the technique itself. This research was quantitative. The method used in this research was by using test to collect instruments in collecting data. From the results of the research, it can be concluded that the students really like learning by using animated videos or cartoons. The respondents also are very positive about this media and students became more active in learning English. In conclusion, the use of video can be applied to all students.